IMPLEMENTASI PENDIDIKAN TAUHID KELAS I SDIT AR-RISALAH KARTASURA TAHUN PELAJARAN 2013/2014 - Marsudi, Saring; Mutsana, Fatimah Umi (Universitas Muhammadiyah Surakarta, 2014)
National education serves to develop skills and form the character and civilization ofdignity in the context of the intellectual life of the nation, aimed at developing thepotential of students to become a man of faith and fear to Allah the Lord, noble, healthy,knowledgeable, skilled, creative, independent, and become citizens of a democratic andresponsible ( Education Law , Article 3 ). This means that the education at primaryschool level should refer to the planting of monotheism in order to achieve educationalgoals fully. The purpose of this study to determine the level of implementation of monotheismin the first grade SDIT Ar -Risalah Kartasura. This research is qualitative research.The data collection methods include observation, interviews, and documentation.This qualitative descriptive data analysis technique emphasize on deductive andinductive inference .The results showed that the content of Tauhid on SDIT Ar-RisalahKartasura are summarized in Aqidah Morals compiled based on salafusshalih which issourced from the Qur’an and Sunnah. Application of monotheism in the learning educationat the first grade conducted with a variety of visual images method , and Shirohstory ( history ). Evaluation of learning is done with the test methods and non test , andcomplies with the assessment standards based on the achievement of the indicators thathave been formulated , including cognitive, affective , and psychomotor